Three-dimensional discrete element analysis of triaxial tests and wetting tests on unsaturated compacted silt. (May 2018) - Li, Tao; Jiang, Mingjing; Thornton, Colin
Abstract: Three-dimensional DEM (discrete element method) simulations of triaxial tests and wetting tests on unsaturated silt were carried out in order to analyse the macro and microscopic behaviour under triaxial stress conditions. Interparticle adhesive forces were incorporated into a rolling and twisting resistance model to represent the van der Waals and capillary forces. A loose DEM sample was first produced considering rolling and twisting resistance and van der Waals forces to sustain an open structure. A series of pseudo-constant water content triaxial tests were simulated by controlling adhesive forces at contacts using the matric suction and a group of representative soil-water characteristic curves. The wetting tests were performed by quickly and gradually wetting (QW and GW) the unsaturated sample at different deviator stress levels. By introducing adhesive forces at contacts, the simulation reproduces the main mechanical behaviour. In the triaxial tests, Z m (mechanical coordination number) for the unsaturated sample increases rapidly during shear until becoming approximately constant. The induced structural anisotropy (under deviatoric loading) reduces with decrease in water content due to the higher interparticle adhesive forces. In the gradual wetting tests, the deviatoric fabric increases gradually during wetting. The deviator strains induced by QW and GW (loading-wetting sequence) are much larger than for the saturated sample at the same stress state in triaxial tests (wetting-loading sequence).